Research and Implementation of Network Topology Visualization Based on H3 - Fuguo Xin; Rongfang Li; Zhongzhen Wang; Dongxiao Quan (Dianxin kexue)
A network topology discovery algorithm was given which had the characteristic of rapid and less extra traffic. The path data were stored by database to facilitate the retrieval and processing of data. Then based on the principle of H3 visualization, the source data was processed to get the needed input file. Finally the network topology was displayed in the hyperbolic space. The test results show that the method is suitable for the network topology visualization, and it can display the network topology beautifully.